Mechanochemical preparation of kaempferol intermolecular complexes for enhancing the solubility and bioavailability. (2nd December 2018) - Xu, Wenhao; Wen, Murong; Yu, Jingbo; Zhang, Qihong; Polyakov, Nikolay E.; Dushkin, Alexandr V.; Su, Weike
Abstract: In this study, complexes of kaempferol (KF) with polysaccharide arabinogalactan (AG) and disodium glycyrrhizinate (Na2 GA) were prepared through mechanochemical technique to improve the solubility and bioavailability of KF. The physicochemical properties and the interactions of KF with AG/Na2 GA were investigated through dissolution, SEM, XRD, and DSC studies. The reduction of particle sizes and destruction of crystal forms revealed the formation of solid dispersion which may have assisted the dissolution of the drug. The accelerated stability study showed higher stability for KF–Na2 GA complex. In vivo pharmacokinetic study was performed to observe the plasma drug concentrations for KF complexes. Mechanochemical complexation of KF with AG/Na2 GA improved the pharmacological activity as evident by the inhibitory potential of the complexes towards carbohydrate metabolic enzymes. In vivo studies were performed in STZ-induced diabetic mice, where the group treated with KF–AG complex showed better liver and kidney function and lower blood glucose levels than pure KF. Therefore, mechanochemical complexes of KF with polysaccharide or glycyrrhizate may serve as a promising formulation for the treatment of diabetes.